EFFECT OF MOTIVATION TOWARD TEACHERâS PERFORMANCE THAT IS MODERATED BY WORK ENVIRONMENT AND ACADEMIK SUPERVISION ( Studies in the District Education Office Pamotan UPT ) - Mokhamad Sarmadi, 13.5202.0023; Suhari, Yohanes (Jurnal Mahasiswa Pasca Sarjana, 2015)
The purpose of this study was to analyze the effect of motivation toward Teacherâs performance that is moderated by work environment and academik supervision ( Studies in the District Education Office Pamotan UPT ). The population in this study is that there are teachers in the target areas 1,2.3.4 and 5 Pamotan the District Education Office UPT number of 196 teachers . Sampling was purposive sampling method , which is based on sampling a particular purpose . The criteria used were sampled by taking a sample of employees who have had a minimum term of 5 years . So the number of samples obtained by 132 people. Mechanical testing data used include test validity , reliability testing , test asumsi classicÂ  , the coefficient of determination and significance test to validate the research hypothesis and test moderation . Research shows that Motivation doesnât affect toward teacherâs performance, work environment dosnât affect toward teacherâs performance, academic supervision affect positively and significantly toward teacherâs performance, variable of work environment become moderation variable, the effect of motivation toward teacherâs performance, variable of academic supervision doesnât become moderation variable, the effect of motivation toward teacherâs performance. Â  Keywords: motivation , work environment , academik supervision and teacherâs performance